Supporting small firms through recessions and recoveries - Bonfim, Diana (2022)
We use variation in the access to a government credit certification program to estimate the financial and real effects of supporting small firms. This program has been implemented during the global financial crisis, but has remained active ever since, allowing us to analyze its effects both during recessions and recoveries. Eligible firms have access to government loan guarantees and a credit quality certification. We estimate real effects using a multidimensional regression discontinuity design. We find that eligible firms borrow more and at lower rates than non-eligible firms, allowing them to increase investment and employment during crises. Industry-level analysis shows reduced productivity heterogeneity in more exposed industries, which is consistent with improved credit allocation. However, when the economy is recovering the effects of the program are less pronounced and centered on the certification component..